What do dental students know about trauma?. Issue 6 (30th June 2015) - AlZoubi, Fahad; Mannocci, Francesco; Newton, Tim; Manoharan, Andiappan; Djemal, Serpil
Abstract: Aim: To assess the baseline knowledge, knowledge acquisition and retention of dental undergraduate students in dental trauma, and the impact of a lecture on their level of confidence in managing traumatic dental injuries. Material and methods: A total of 145 dental undergraduate students from King's College London were invited to attend a lecture on dental trauma. The participants were asked to complete a questionnaire on dental trauma before (T0), immediately after (T1) and 6 months (T2) following a 1‐h lecture. Results: Seventy of the 145 students participated in the study. The level of knowledge at T0, T1 and T2 was 64.9%, 83.2% and 69.5%, respectively. The increase in score was statistically significant between T0 and T1, and between T0 and T2. A significant decrease in score was also found between T1 and T2. Sex, level of education and whether or not the participants received previous teaching in dental trauma were not significant in predicting a change in score. The level of confidence increased significantly from 2.14 at T0 to 3.13 at T2. Participants who received teaching in dental trauma previous to the lecture were significantly more confident at T0. Conclusions: Lectures are effective at improving the knowledge and retention of knowledge of dental undergraduate students in dental trauma. However, retention of the knowledge is time limited suggesting that education should be repeated after a certain period of time to ensure that a high level of knowledge is maintained.